Real-Time Laboratory with a STEM Approach: A Social Semiotic and Quantitative Analysis of Their Impact on Graphical Competence in Kinematics among Upper Secondary Students - Sarmiento, Sergio R. Betanzos; Mora, Cesar; Magallanes, Fermin Acosta (Journal of Posthumanism, 2025)
In this mixed-methods study, we evaluate the impact of the Real-Time Laboratory (RTL) with a STEM approach, implemented using Arduino technology, on conceptual learning and the development of graphical competence in one-dimensional kinematics among upper secondary students. The intervention follows a methodology based on prediction, experimentation, comparison, and data analysis, which is characteristic of RTL. Additionally, we rely on Social Semiotics to provide evidence of how students use RTL and the types of interactions that occur around it concerning tasks related to the interpretation and construction of kinematic graphs. This contribution is relevant as it assesses the pertinence of RTL as both a semiotic and didactic resource to achieve this goal.